Mechanical Parameters and Trajectory of Two Chinese Cervical Manipulations Compared by a Motion Capture System - Huang, Xuecheng; Lin, Dongxin; Liang, Zeyu; Deng, Yuping; He, Zaopeng; Wang, Mian; Tan, Jinchuan; Li, Yikai; Yang, Yang; Huang, Wenhua (Frontiers in Bioengineering and Biotechnology, 2021)
Objective. To compare the range of cervical spine motion and clinical safety while operating the oblique pulling manipulation and the cervical rotation–traction manipulation. Methods. An experimental research measuring kinematics parameter and recording motion trajectories of two cervical manipulations were carried out. A total of 48 healthy volunteers participated in this study, who were randomly divided into two groups of 24 representing each of the two manipulations. A single manipulator operated two manipulations in two groups separately. A motion capture system was used to monitor and analyze kinematics parameters during the operation. Results. The two cervical manipulations have similar thrust time, displacement, mean velocity, max velocity, max acceleration. There were no significant differences in active and passive range of motion between the two cervical rotation manipulations. The thrust range of motion of the oblique pulling manipulation and the cervical rotation–traction manipulation were 5.735±3.041 and 2.142±1.742, respectively. The thrust range of motion of the oblique pulling manipulation was significantly greater than that of the cervical rotation–traction manipulation (P<0.001). Conclusion. Compared with the oblique pulling manipulation, the cervical rotation–traction manipulation has a less thrust range of motion that reduces the potential risk of cervical manipulation and is clinically safe.